Chronic Daily Headache in Korea: Prevalence, Clinical Characteristics, Medical Consultation and Management - Park, Jeong-Wook (Korean Neurological Association, 2014)
BACKGROUND AND PURPOSE: Chronic daily headache (CDH) is a commonly reported reason for visiting hospital neurology departments, but its prevalence, clinical characteristics, and management have not been well documented in Korea. The objective of this study was to characterize the 1-year prevalence, clinical characteristics, medical consultations, and treatment for CDH in Korea. METHODS: The Korean Headache Survey (KHS) is a nationwide descriptive survey of 1507 Korean adults aged between 19 and 69 years. The KHS investigated headache characteristics, sociodemographics, and headache-related disability using a structured interview. We used the KHS data for this study. RESULTS: The 1-year prevalence of CDH was 1.8% (95% confidence interval, 1.1-2.5%), and 25.7% of the subjects with CDH met the criteria for medication overuse. Two-thirds (66.7%) of CDH subjects were classified as having chronic migraine, and approximately half of the CDH subjects (48.1%) reported that their headaches either substantially or severely affected their quality of life. Less than half (40.7%) of the subjects with CDH reported having consulted a doctor for their headaches and 40.7% had not received treatment for their headaches during the previous year. CONCLUSIONS: The prevalence of CDH was 1.8% and medication overuse was associated with one-quarter of CDH cases in Korea. Many subjects with CDH do not seek medical consultation and do not receive appropriate treatment for their headaches.